(untitled) (Bulletin KNOB, 2017)
In 1989, during excavations of the site of the Mariakerk in Diemen, which was demolished in 1808, over one-hundred-and-fifty, remarkably good quality, architecture and sculpture fragments came to light. They are the remains of an exceptionally refined Sacrament House that was probably destroyed during the Reformation. It was composed of many vertical elements and of painted and gold-leaf-embellished figures. Judging from the style and iconography, it probably originated in Utrecht around 1460/70. The sculpture seems too opulent for a parish as small and impoverished as Diemen was at that time. Because of indications that the object in question had been dismantled and reassembled, its location in Diemen suggests that it was a secondhand Sacrament House, since outmoded Sacrament Houses from wealthier church establishments were often sold on to smaller churches when their design went out of fashion. Thus the object will have originally been made for a more prestigious setting. Given the links between the Diemen and Utrecht Maria churches (the provost of the Utrecht Mariakerk appointed the Diemen priest), it is quite conceivable that the Sacrament House came originally from the Mariakerk in Utrecht. At any rate, in 1516 a grand new Sacrament House, measuring no less than 30 feet, was ordered for the Utrecht Mariakerk. An older Sacrament House would not simply be thrown away, but sold or turned over to one of its own parish churches. Its transfer to Diemen is a possibility that merits serious consideration. If that was in fact what happened, a Utrecht-made Sacrament House, possibly from Utrecht’s Mariakerk, led a second life of some forty years in Diemen from circa 1516 to 1566, until being smashed to smithereens during the Protestant Iconoclasm. While the surviving fragments may be too small to enable the Sacrament House to be reconstructed, they are big enough to continue to tell their own story, notwithstanding the Iconoclasm and possible later mishandling of the object.